What to expect when you are not expecting to be a publisher. Issue 3 (5th August 2014) - L. De Groote, Sandra; M. Case, Mary
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to outline the evolution of University of Illinois at Chicago's (UIC) journal hosting service from the initial phase of setting up a server to host journals through to the point of offering a suite of library publishing services. The UIC has been hosting Internet-based journals since the 1990s. Design/methodology/approach – In this study, challenges and steps taken for inclusion in PubMed, archiving in PubMed Central and developing policies and parameters of support are discussed. Findings – Venturing into the world of Library as Publisher is not the decision that should be taken lightly, but supporting affordable scholarly publishing, when successful, is rewarding. Originality/value – This paper will be of value to libraries considering offering journal hosting services.